2021
DOI: 10.1186/s12935-021-02167-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of XBP-1-mediated unfolded protein response in colorectal cancer progression-a regulatory mechanism associated with lncRNA-miRNA-mRNA network

Abstract: Background We aim to identify the expression and analyze the molecular action of dysregulated lncRNA-miRNA mediated by XBP-1 in colorectal cancer (CRC). Methods Here, we identified XBP-1-mediated dysregulated lncRNAs and miRNAs in CRC by bioinformatics analysis. The expression level of lncRNAs and miRNA was measured using quantitative real time PCR, and the expression of XBP-1, as well as apoptosis-related proteins, were detected by western blot. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…In another part of the study, increased expression of KCNQ1OT1/XIST showed the effects of inhibiting XBP1 on the loss of viability of colorectal cancer cells and inhibition of apoptosis. Overall, Y. Wang et al (2021) in this study found that KCNQ1OT1/XIST accelerated tumor growth by regulating ER stress and cellular apoptosis in colorectal cancer in vitro and in vivo.…”
Section: Role Of Lncrnas In Apoptosis and Proliferationsupporting
confidence: 53%
See 1 more Smart Citation
“…In another part of the study, increased expression of KCNQ1OT1/XIST showed the effects of inhibiting XBP1 on the loss of viability of colorectal cancer cells and inhibition of apoptosis. Overall, Y. Wang et al (2021) in this study found that KCNQ1OT1/XIST accelerated tumor growth by regulating ER stress and cellular apoptosis in colorectal cancer in vitro and in vivo.…”
Section: Role Of Lncrnas In Apoptosis and Proliferationsupporting
confidence: 53%
“…In a recent study, the role of XBP1 in regulating the expression of lncRNA networks in colorectal cancer was investigated (Ebrahimi, Rezanejad, et al, 2022; Y. Wang et al, 2021). With increasing XBP1 expression in colorectal cancer cell lines, six lncRNAs including NEAT1, SLFNL1‐AS1, XIST, KCNQ1OT1, AC026362.1, and AC016876.2 showed decreased expression.…”
Section: Role Of Lncrnas In Apoptosis and Proliferationmentioning
confidence: 99%
“…In fact, growing evidence linking pathological conditions to lncRNAs and their regulatory network is emerging, especially in cancer development and progression, with important implications in diagnostics and therapeutics. Specifically, different studies report the correlation of XIST expression with prognosis such as in the case of colon and gastric cancer, glioma and cervical and ovarian cancer [ 65 , 66 , 67 , 68 , 69 , 76 , 77 , 78 , 79 , 83 , 84 , 85 , 86 ] or FTX expression and gastric cancer prognosis [ 179 ] or JPX expression and poor survival of lung cancer patients [ 188 , 189 ]; probably, combination of the expression values of more than one RNA molecule involved in the same regulatory axis could enhance the diagnostic power, e.g., making it possible to stratify the patients according tumor stage, favorable/unfavorable outcome and even therapy effectiveness. Finally, understanding the versatility of RNA biology has become a stepping stone for RNA therapeutics that has definitely demonstrated its power [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, the XIST ceRNA activity is also involved in chemoresistance: as an example, XIST competes with serum and glucocorticoid-inducible kinase 1 (SGK1) by sponging the shared miR-124, and thus enhancing doxorubicin resistance [ 66 ]. Recently, complex lncRNA/miRNA/mRNA networks based on XIST/miR-500a-3p, miR-370-3p, miR-2467-3p, miR-512-3p/XBP have been demonstrated to promote cell proliferation and aggravated tumor growth in vivo by regulating endoplasmic reticulum stress response and cell apoptosis [ 67 ].…”
Section: Cerna Activity Of the Lncrnas From The Xicmentioning
confidence: 99%
“…At the post‐transcriptional level, lncRNAs could act as molecular sponges that function as competing endogenous RNAs (ceRNAs) by competitively occupying the shared binding sequences of miRNAs, thereby sequestering miRNAs and altering the expression of their downstream target genes. Mechanistically, CRC‐related lncRNAs proved to be activated or inhibited through epigenetic modification, lncRNA‐miRNA‐mRNA, lncRNA‐ceRNA, lncRNA‐protein, regulation of Wnt/β‐Catenin signaling pathway (Li, Mu, Shi, & Xin, 2021; Qi, Lin, Liu, Chen, & Shen, 2020; Wang, Zhang, & Zheng, 2021). Functionally, lncRNAs exhibit four main regulatory roles, namely, signal, decoy, guide, and scaffold to regulate gene expression (Ming, Li, Zhou, Goel, & Huang, 2021).…”
Section: Flavonoids Prevent Crc Mediating By Lncrnasmentioning
confidence: 99%